2006
DOI: 10.1002/bem.20262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field on the antioxidant enzyme activities of suspension‐cultured tobacco cells

Abstract: Effects of magnetic fields (MFs) on the activities of antioxidant enzymes of suspension-cultured tobacco cells were investigated. Compared with the control cells, exposure of the cells to static MF with the magnitudes of 10 and 30 mT for 5 days, 5 h each day, increased the activity of superoxide dismutase (SOD). In contrast, the activity of the catalase (CAT) and ascorbate peroxidase (APX) was decreased by MF, compared with those of the control cells. Level of lipid peroxidation was also increased by MF. It su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 31 publications
3
77
2
1
Order By: Relevance
“…The optimal intensity is 3 mT SMF. These data are consistent with those which described by Sahebjamei et al [2007]. Similar to our results, the increased activity of superoxide dismutase and catalase activity was detected after long-term influence of magnetic field on suspension-cultured of tobacco cells.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The optimal intensity is 3 mT SMF. These data are consistent with those which described by Sahebjamei et al [2007]. Similar to our results, the increased activity of superoxide dismutase and catalase activity was detected after long-term influence of magnetic field on suspension-cultured of tobacco cells.…”
Section: Resultssupporting
confidence: 94%
“…Therefore, the impact of any stressors during seed germination can be displayed on the further development of the plant [Sahebjamei et al 2007]. Active forms of oxygen are always present in plant organism and can interact with different biological compounds to form free radicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MACS use involves the passage of sperm through a high power static magnetic field (SMF) of 0.5 T and up to 1.5 T [82,83]. Several researches have shown that SMF can generate some kind of effect on biological systems, as pro-inflammatory changes and increase in the generation of ROS [84][85][86], which is highly detrimental to sperm. Although the mechanism by which SMF affects cells is not well understood, some reports speculate that it might increase the activity, concentration, and life time of paramagnetic free radicals, which could ultimately produce oxidative stress, genetic mutations, and/or apoptosis [87][88][89].…”
Section: How Does Macs Work?mentioning
confidence: 99%